Expression Levels of lncRNAs in the Patients with the Renal Transplant Rejection - Nafar, Mohsen; Kalantari, Shiva; Ghaderian, Sayyed Mohammad Hossein; Omrani, Mir Davood; Fallah, Hamid; Arsang-Jang, Shahram; Abbasi, Tahereh; Samavat, Shiva; Dalili, Noshin; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Urology Journal, 2019)
Purpose: Long non-coding RNAs (lncRNAs) include a vast portion of human transcripts. They exert regulatory roles in immune responses and participate in diverse biological functions. Recent studies indicated dysregulation of lncRNAs in the process of transplant rejection. In the current study, we aimed at identification of the expression of five lncRNAs (OIP5-AS1, FAS-AS1, TUG1, NEAT1 and PANDAR) in association with the process of transplant rejection. Material and Methods: We assessed expression of these lncRNAs in the peripheral blood of 61 kidney transplant receivers including 29 transplant rejected patients and 32 transplant non-rejected patients using real time PCR technique. Results: Expression of FAS-AS1 was significantly higher in rejected group compared to non-rejected group in males, however, differences between case and control groups were insignificant among females. For other lncRNAs no significant differences were detected between two study groups. Quantile regression model showed that patients’ gender was an important parameter in determination of FAS-AS1 expression (Beta=-9.46, t=-2.82, P=0.007) but not for other lncRNAs expressions. Significant pairwise correlations were detected between expression levels of lncRNAs in a disease related manner. Conclusion: Based on the higher expression of FAS-AS1 in patients with transplant rejection, this lncRNA might be associated with the pathogenesis of renal transplant rejection.